An Exploration of Speech-Based Productivity Support in the Car - Martelaro, Nikolas; Iqbal, Shamsi; Teevan, Jaime (CHI 2019, 2019)
In-car intelligent assistants offer the opportunity to help drivers productively use previously unclaimed time during their commute. However, engaging in secondary tasks can reduce attention on driving and thus may affect road safety. Any interface used while driving, even if speech-based, cannot consider non-driving tasks in isolation of driving—alerts for safer driving and timing of the non-driving tasks are crucial to maintaining safety. In this work, we explore experiences with a speech-based assistant that attempts to help drivers safely complete complex productivity tasks. Via a controlled simulator study, we look at how level of support and road context alerts from the assistant influence a driver’s ability to drive safely while writing a document or creating slides via speech. Our results suggest ways to support speech-based productivity interactions and how speech-based road context alerts may influence driver behavior.